Agaricus blazei Water Extracts as Alternative Medicines - Sorimachi, Kenji; Koge, Takashi (Current Pharmaceutical Analysis, 2008)
A great amount of attention has recently been given to the water extracts of the basidiomycete Agaricus blazei, a kind of mushroom, to evaluate the applicability of their biological activity as an alternative medicine. Agaricus blazei is native to Brazil and was imported to Japan in 1965. Since Agaricus blazei was first cultured at Iwade Mycology Institute in Japan in 1975, its biological activity spectrum has been evaluated not only in in vivo, but also in in vitro experiments. Antitumor activity was first detected in Agaricus blazei water extracts in 1980. Since then, many groups have reported this antitumor activity, which results from polysaccharides such as β-D-glucans and their derivatives. In general, the antitumor activity appears to be mainly due to the activation of the immune system rather than to any direct effects of the water extracts on tumor cells. This idea is supported by the fact that macrophages derived from rat bone marrow were activated and cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1 (IL-1) and IL-8, and nitric oxide (NO) were secreted, in response to these water extracts in in vitro experiments. Furthermore, oral administration of Agaricus blazei water extracts to mice induced the activation of macrophages and T cells in vivo. Anti-genotoxic, anti-mutagenic and anticlastogenic effects were also detected in Agaricus blazei water extracts. As well, anti-viral activity of Agaricus blazei hypha water extracts was observed on the cytopathic effects induced by Western Equine Encephalitis (WEE) virus in vitro. Thus, based on both in vivo and in vitro experiments, Agaricus blazei water extracts appear to have great potential for development as alternative medicines.
Keywords: Antitumor activity